2010
DOI: 10.1590/1808-1657v77p6352010
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento De Genótipos De Feijoeiro Ao Ataque De Bemisia Tabaci (Genn.) Biótipo B (Hemiptera: Aleyrodidae)

Abstract: RESUMO Avaliou-se o comportamento de genótipos de feijoeiro sob infestação de Bemisia tabaci (Genn.) biótipo B em condições de campo, nas épocas de cultivo “da seca” e “das águas”. Utilizaram-se os genótipos IAC-Tybatã, IAC-Una, FT-Nobre, Pérola, LP 98-122, LP 02-130, LP 01-38, LP 9979, BRS-Pontal, BRS-Requinte, BRS-Triunfo, BRS-Grafite, CV-48 e Z-28. Adotou-se o delineamento de blocos casualizados com 14 tratamentos e três repetições. As avaliações foram realizadas semanalmente, contando-se o número de ovos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Thus, MEAM1 adults will likely acquire the best nutrients for development during seedling stage of the squash and zucchini, which explains the highest number of adult MEAM1 in earlier weeks. Our findings align with previous studies [ 25 , 41 , 70 ] that found adult whitefly infestations were higher in the early stage of the plants.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, MEAM1 adults will likely acquire the best nutrients for development during seedling stage of the squash and zucchini, which explains the highest number of adult MEAM1 in earlier weeks. Our findings align with previous studies [ 25 , 41 , 70 ] that found adult whitefly infestations were higher in the early stage of the plants.…”
Section: Discussionsupporting
confidence: 93%
“…This is the first study to determine the population dynamics of multiple pests, pollinators, and natural enemies on 24 local and commercially available bush snap bean cultivars in the southern United States. Previous studies concentrated on determining the susceptibility of different snap bean cultivars to only one major pest, such as B. tabaci [ 11 , 12 , 13 , 30 ], E. fabae [ 15 , 38 ], or L. lineolaris [ 39 , 40 ]. Therefore, this study might contribute to the knowledge of the population dynamics of insect pests and beneficials as impacted by the cultivation of snap bean cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Host plant resistance, where crops are bred or genetically engineered to reduce pest damage, has become an essential pest management tool [ 10 ]. Several snap bean cultivars have demonstrated certain levels of resistance to some pests including the sweetpotato whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) Middle East-Asia Minor 1 [ 11 , 12 , 13 ]; potato leafhopper, Empoasca fabae (Harris) (Hemiptera: Cicadellidae) [ 14 , 15 ]; Mexican bean beetle, Epilachna varivestis (Mulsant) (Coleoptera: Coccinellidae) [ 16 ]; and European corn borer [ 17 ]. For instance, the lowest number of B. tabaci eggs per leaf disc was observed on snap bean cultivar ‘Jade’, whereas cultivars ‘Gold Mine’, ‘Golden Rod’, ‘Long Tendergreen’, and ‘Royal Burgundy’ supported a significantly lower number of B. tabaci nymphs per leaf disc in the 2020 fall season in Georgia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%